2021
DOI: 10.1016/j.waojou.2021.100559
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity assessment and allergen profile analysis of different Chinese wheat cultivars

Abstract: Backgrounds As one of the most important cereals, wheat ( Triticum aestivum ) can cause severe allergic reactions, such as baker's asthma, allergic rhinitis, and atopic dermatitis. A growing number of people are developing allergies to Chinese wheat; however, only a few wheat cultivars have been screened on allergenicity in China. Objective The aim of the present study was to assess the allergenicity of different Chinese wheat cultivars and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…When dealing with bakers allergic to wheat flour, other variables should be considered like the specific wheat cultivars utilized in milling, and other factors that could produce different allergen content and expression in flours. Although it seems that there are no clinically significant differences in the allergenicity of wheat of different species, without considering the more than 25,000 cultivars, the different clinical symptoms and allergenassociated could vary with the different wheat species or patients in different regions [29,30]. In addition, different populations may show different responses to allergens in relationship to other environmental factors or genetic characteristics [31].…”
Section: Discussionmentioning
confidence: 99%
“…When dealing with bakers allergic to wheat flour, other variables should be considered like the specific wheat cultivars utilized in milling, and other factors that could produce different allergen content and expression in flours. Although it seems that there are no clinically significant differences in the allergenicity of wheat of different species, without considering the more than 25,000 cultivars, the different clinical symptoms and allergenassociated could vary with the different wheat species or patients in different regions [29,30]. In addition, different populations may show different responses to allergens in relationship to other environmental factors or genetic characteristics [31].…”
Section: Discussionmentioning
confidence: 99%
“…The term "allergy" describes an adverse immune response initiated by the host's immune system upon exposure to a given substance that is generally harmless in the environment. Statistical analysis has shown that allergen-induced food allergies affect approximately 2.5% (ranging from 1% to 10%) of the world's general population (1)(2)(3). Over the past several decades, food allergy has emerged unexpectedly as a "second wave" of the allergy epidemic, with an increasing number of infants and children afflicted with the disease from developing and developed countries worldwide (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, plant genes were analyzed that are homolo gous to three T. aestivum genes encoding food allergens β-amylase, albumin, and globulin, earlier identified as targets for human IgE (Wang et al, 2021). Thus, 363 homologous genes were investigated belonging to 28 and 15 species of food plants and nonfood plants, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide sequences of plant gene promoters analyzed in this work. Three allergenic proteins from common wheat T. aestivum were investigated: β-amylase, albumin, and globu lin, which have previously been experimentally identified as targets for human class E immunoglobulins (Wang et al, 2021). From the GenBank database (Benson et al, 2015), nu cleotide sequences of 90 bp proximal promoters were retrieved that are located immediately upstream of transcription start sites of plant genes homologous to the genes of β-amylase, albumin, and globulin from common wheat T. aestivum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation